Pengggunaan Metode Guided Note Taking dalam Peningkatan Pembelajaran PAI - Titin Wijayanti (LPPM Institut Agam Islam Nahdlatul Ulama (IAINU) Kebumen, 2023)
The purpose this research in increasing Islamic ecucation zakat and whole number in the students class VI of SD Negeri Karangjambu by using Guided Note Taking. The type of this research is Classroom Action Research (CAR) during 3 cycles, each cycle includes of planning, implementation, observation, and reflection. As sample is students class VI of SD Negeri Karangjambu, it includes 22 students. Technique of collecting data is used observation, interview, test, and documentation. The result shows that using Guided Note Taking could increase Islamic ecucation zakat and whole number.